The Geriatric-8 (G8) screening questionnaire as a predictor of anticancer therapy toxicity in elderly patients: a comprehensive analysis of current data - A. B. Elmurzaev; I. N. Danilov; I. V. Rykov; G. A. Chizh; T. P. Nikitina; S. O. Kuzin; O. S. Lokotosh; V. A. Mirgorodskaya (Malignant tumours, 2026)
Introduction. Treatment of elderly cancer patients is challenging due to high risk of adverse events. Comprehensive Geriatric Assessment (CGA) is the gold standard but time-consuming. The G8 screening tool rapidly identifies patients requiring CGA. Aim. To summarize current evidence on the predictive value of the G8 for chemotherapy toxicity, assess its diagnostic accuracy, compare it with other geriatric scales, and evaluate its applicability in the Russian population. Materials and methods . A systematic search of PubMed, Google Scholar, eLibrary, and CyberLeninka (2012–2024) was performed. Prospective cohort studies, RCTs, meta-analyses, and validation studies of the G8 were included; 40 publications met the inclusion criteria. Results. A G8 score ≤ 14 is associated with a 2.3‑fold increased risk of grade 3–4 toxicity (OR 2.3; 95 % CI 1.7–3.1) and significantly worse overall survival (HR 2.72; 95 % CI 1.89–3.91; p < 0.001). Pooled sensitivity for detecting geriatric impairments is 74–89 %, specificity 55–65 %. The Russian version demonstrated good internal consistency (α = 0.709). Compared with CARG and CRASH, the G8 is best suited for first-line screening (AUC 0.72–0.85), while CARG / CRASH refine toxicity prediction before chemotherapy (AUC 0.65–0.72). Conclusion . The G8 is a valid, reliable screening tool for risk stratification and selection for CGA. Its combination with CARG / CRASH provides an evidence-based approach to managing older adults with cancer. Further validation studies of CARG and CRASH in the Russian population are required.